Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XIX): The identity of D. calthifolium from northern Sichuan - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2019)
Based on examination of herbarium specimens (including type material), we found that Delphinium calthifolium (Ranunculaceae), described from northern Sichuan in China, is conspecific with D. sinovitifolium, a species known only from its type material and misunderstood for a long time. We therefore place D. calthifolium in synonymy with D. sinovitifolium herein.